Penggunaan Metode Jarimatika Dalam Meningkatkan Kemampuan Berhitung Perkalian Dasar - Dwi Rahmayanti, Jesica (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This study aims to determine the increase in students' numeracy skills on basic multiplication material through the jarimatics method in class II SD Muhammadiyah I Menganti Gresik. This research was conducted in class II of SD Muhammadiyah 1 Menganti Gresik for the 2022/2023 academic year. which totaled 26 students, consisting of 15 male students, and 11 female students. The research lasted for one month, from January 10 to February 10 2023. In collecting data, researchers used observation, testing and documentation techniques. The instruments used were observation sheets and learning achievement test sheets. The results showed that the jarimatics method could improve students' numeracy skills in basic multiplication material in class II Muhammadiyah 1 Menganti Gresik Elementary School. This can be proven based on the percentage results from cycle I to cycle II. In the pre-cycle there were only 12 students who achieved the minimum completeness criteria with a percentage of 46%, while those who did not complete were 14 students with a percentage of 54%. In cycle I there were 16 students who succeeded in achieving minimum completeness with a percentage of 65%, and students who had not completed as many as 10 students so that they achieved a percentage of 38%. From the results of the pre-cycle to cycle I, it increased by a percentage of 16%. Whereas in cycle II, there were 23 students out of a total of 26 students who achieved the minimum completeness criteria, so the percentage of students who completed was 88%, while the number of students who had not reached the minimum completeness criteria was 3 students with a percentage of 12%. So, learning outcomes from cycle I to cycle II increased by 62%.